Development of a Nucleotide Exchange Inhibitor That Impairs Ras Oncogenic Signaling. Issue 7 (27th December 2016) - Marín‐Ramos, Nagore I.; Piñar, Carmen; Vázquez‐Villa, Henar; Martín‐Fontecha, Mar; González, Ángel; Canales, Ángeles; Algar, Sergio; Mayo, Paloma P.; Jiménez‐Barbero, Jesús; Gajate, Consuelo; Mollinedo, Faustino; Pardo, Leonardo; et al.
Abstract: Despite more than three decades of intense effort, no anti‐Ras therapies have reached clinical application. Contributing to this failure has been an underestimation of Ras complexity and a dearth of structural information. In this regard, recent studies have revealed the highly dynamic character of the Ras surface and the existence of transient pockets suitable for small‐molecule binding, opening up new possibilities for the development of Ras modulators. Herein, a novel Ras inhibitor (compound12 ) is described that selectively impairs mutated Ras activity in a reversible manner without significantly affecting wild‐type Ras, reduces the Ras–guanosine triphosphate (GTP) levels, inhibits the activation of the mitogen‐activated protein kinase (MAPK) pathway, and exhibits remarkable cytotoxic activity in Ras‐driven cellular models. The use of molecular dynamics simulations and NMR spectroscopy experiments has enabled the molecular bases responsible for the interactions between compound12 and Ras protein to be explored. The new Ras inhibitor binds partially to the GTP‐binding region and extends into the adjacent hydrophobic pocket delimited by switch II. Hence, Ras inhibitor12 could represent a new compound for the development of more efficacious drugs to target Ras‐driven cancers; a currently unmet clinical need. Abstract : All bound up : The oncogenic activity of mutated Ras is impaired by a new inhibitor, which reduces the Ras–guanosine triphosphate (GTP) levels, inhibits the mitogen‐activated protein kinase (MAPK) pathway, and is cytotoxic in Ras‐driven cellular models (see figure). This new inhibitor adds to the scarce number of compounds available to fight Ras‐driven cancers; a currently unmet clinical need.